Mexican physical education teacher's self-reported and self-perception of teaching style - Oscar Núñez Enríquez; Julio César Guedea-Delgado; Gabriel Gastelum-Cuadras; Ena Monserrat Romero-Pérez; Ramón Candia Luján; Raúl Josué Nájera-Longoria (Colégio Brasileiro de Ciências do Esporte, 2021)
ABSTRACT To understand the self-reported and perception of teaching style used among Mexican physical education teachers. Participants included 104 (n=41 females and 63 males) elementary physical education teachers from northern Mexico. Results showed that a traditional teaching style tends to be mainly used either by male and female's physical education teachers. Showing differences between genders and teaching styles. Female teachers tend to combine a traditional teaching style with one that connects with students engaging in physical activity, developing positive values and attitudes. Cultural context plays an important aspect when developing a teaching self-perception.